2016
DOI: 10.1007/s10286-016-0385-3
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic dysfunction in pediatric patients with headache: migraine versus tension-type headache

Abstract: The need for prospective research investigating autonomic dysfunction in pediatric headache patients is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…21 Although a few studies have assessed the presence of symptoms related to autonomic dysfunction in those with migraine, there is a lack of studies using validated questionnaires to broadly assess symptoms of autonomic dysfunction in migraine. 32,34,36 The total COMPASS-31 scores of the individuals with PPTH in this study suggest fairly severe symptoms of autonomic dysfunction, a severity comparable to patients with confirmed small fiber polyneuropathies. The mean total weighted COMPASS-31 score of our PPTH group was 37.22, similar to a mean score of 38.8 in patients with small fiber polyneuropathy in the study by Treister et al, 40 and less than the 48.05 in POTS subjects, and 50.82 in autonomic failure subjects in the study by Rea et al 48 While the average score of the aforementioned POTS and autonomic failure subjects were higher, the interquartile To our knowledge, there are no prior studies comparing PPTH or mTBI with migraine populations with regards to symptoms of autonomic dysfunction.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…21 Although a few studies have assessed the presence of symptoms related to autonomic dysfunction in those with migraine, there is a lack of studies using validated questionnaires to broadly assess symptoms of autonomic dysfunction in migraine. 32,34,36 The total COMPASS-31 scores of the individuals with PPTH in this study suggest fairly severe symptoms of autonomic dysfunction, a severity comparable to patients with confirmed small fiber polyneuropathies. The mean total weighted COMPASS-31 score of our PPTH group was 37.22, similar to a mean score of 38.8 in patients with small fiber polyneuropathy in the study by Treister et al, 40 and less than the 48.05 in POTS subjects, and 50.82 in autonomic failure subjects in the study by Rea et al 48 While the average score of the aforementioned POTS and autonomic failure subjects were higher, the interquartile To our knowledge, there are no prior studies comparing PPTH or mTBI with migraine populations with regards to symptoms of autonomic dysfunction.…”
Section: Discussionmentioning
confidence: 53%
“…Several studies have concluded that migraine is associated with decreased parasympathetic activity with increased sympathetic activity at night, pupillary hypofunction, lack of sympathetic/parasympathetic control, generalized autonomic hypofunction, hyperactivity of parasympathetic and sympathetic nervous system, impaired sympathetic function, sympathetic instability, and sympathetic hyperactivity . Although a few studies have assessed the presence of symptoms related to autonomic dysfunction in those with migraine, there is a lack of studies using validated questionnaires to broadly assess symptoms of autonomic dysfunction in migraine …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…He explained that these symptoms in headache groups is possibly because of sympathetic hyperfunction, as increased sympathetic discharge may activate the small nerve fibers connected to sweat glands to cause excessive sweating. 18 Although numerous studies have documented the presence of ANS dysfunction in primary episodic headaches with special reference to migraine, [5][6][7] the results are conflicting. The most common findings are sympathetic hypofunction, but higher sympathetic tone or parasympathetic dysfunction had also been reported.…”
Section: Discussionmentioning
confidence: 99%